Effect of Doping Cu on the Structural and Optical Properties of (CdTe) Thin Films - Maki, Samir A.; Hasson, Bushra K.; Feyad, Salam H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research we studied the structural and optical properties of (CdTe) thin films which have been prepared by thermal evaporation deposition method on the glass substrate at R.T with thickness (450 ï‚± 25) nm., as a function of doping ratio with copper element in (1,3,5) % rate .The structure measurement by X-ray diffraction (XRD) analyses shows that the single phase of (CdTe) with polycrystalline structure with a preferred orientation [111]. The optical measurement shows that the (CdTe) films have a direct energy gap, and they decrease with the increase of doping ratio reaching to 5% . The optical constants are investigated and calculated, such as absorption coefficient (Î±), refractive index (n) , extinction coefficient (k) and the dielectric constants (Ð„) with both parts real and imaginary for the wavelengths in the range (300-1100) nm, before and after doping processes